PENGARUH LOCUS OF CONTROL EKSTERNAL TERHADAP IMPULSIVEBUYING PADA MAHASISWA DENGAN JENIS KELAMIN SEBAGAI VARIABEL MODERATOR - Lusi Tania Agustin; Sarsono Sarsono (Turast: Jurnal Penelitian dan Pengabdian, 2018)
This study aims to examine the effect of external locus of control based on students’ gender towards impulsive buying. The subjects of this study are 80 students in the Special Region of Yogyakarta, aged 17-21 years. The Impulsive Buying and External Scales of Locus of Control were the instruments of this research. Simple linear regression analysis used as the data analysis. The results showed that external locus of control had a significant influence on impulsive buying in students, with F count of 56.702 and p = 0.000 (0 <0.010). This showed a significant influence between impulsive buying of clothing products with external locus of control on students. There is a positive influence between external locus of control on impulsive buying and gender as a moderator variable. The hypothesis proposed in this study is acceptable. It is concluded that between impulsive buying and external locus of control occurs because of causality or influence each other.